Identifikasi Struktur Bawah Permukaan Menggunakan Geomagnet Wilayah Hot Spring Lau Sigembura Deli Serdang - Mutiara sani; Nazaruddin Nasution; Ridwan Yusuf Lubis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted at the Lau Sigembura hot spring tour, STM Hilir sub-district, Deli Serdang district using the magnetic method. This study aims to determine. Subsurface structures and the distribution of magnetic anomalies which are geothermal manifestations. The number of measurement points is 50 with an area of ​​1000 square meters. Data acquisition was carried out using the PPM Model GEM System type GSM 19T.While data processing uses daily corrections and IGRF corrections as well as upward continuations. Modeling is done using Mag2DC software. The total magnetic field ranges from -900 nT to 500 nT based on the contour of the local magnetic anomaly, the variation in the value of the anomaly is around -1050 nT to 350 nT. While the quantitative interpretation indicates the presence sandstone rock with susceptibility value 0,1075 cgs, Andesit with susceptibility values 0,0183 cgs, limestone with a susceptibility value of 0.0001 cgs – 0.0021 cgs. And shales with susceptibility value 0,021 cgs.